2021
DOI: 10.1097/md.0000000000026330
|View full text |Cite
|
Sign up to set email alerts
|

Operative treatments for osteochondral lesions of the talus in adults

Abstract: Purpose: This systematic review aimed to identify the available evidence regarding the comparative effectiveness and safety of various operative treatments in adult patients with osteochondral lesions of the talus (OLT). Materials and methods: The PubMed, Embase, ISI Web of Knowledge, and the Cochrane Controlled Trial Register of Controlled Trials were searched from their inception date to September 2019. Two reviewers selected the randomized controlled trials (RCTs) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
(148 reference statements)
0
3
0
Order By: Relevance
“…They concluded that augmented microfracture is superior to microfracture alone in treating talar OLTs based on the AOFAS, MOCART, VAS score, complication rate, and revision ratio. Tan et al(66) confirmed the results with a similar methodologic approach.There are also discussions on the best BMS technique. Kraeutler et al(67) concluded after a systematic review and meta-analyses that there is still limited basic science available, whether deep drilling or microfracture leads to better clinical results.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…They concluded that augmented microfracture is superior to microfracture alone in treating talar OLTs based on the AOFAS, MOCART, VAS score, complication rate, and revision ratio. Tan et al(66) confirmed the results with a similar methodologic approach.There are also discussions on the best BMS technique. Kraeutler et al(67) concluded after a systematic review and meta-analyses that there is still limited basic science available, whether deep drilling or microfracture leads to better clinical results.…”
mentioning
confidence: 66%
“…In smaller lesions, the additional scaffolds did not change the clinical outcome. However, patients benefit from biological support (65,66).…”
Section: Discussionmentioning
confidence: 99%
“…Osteochondral lesions of the talus (OLT) are frequently seen in orthopedic practice, with the majority of lesions occurring following a traumatic event, such as an ankle sprain or ankle fracture [1][2][3][4][5][6]. A consensus statement by international experts suggested that a lesion to both the cartilage and underlying subchondral bone of the talus should be referred to as an OLT [6].…”
Section: Introductionmentioning
confidence: 99%